Employee Political Skill, Organizational Citizenship Behaviour and Performance among Employees in Kenyan Universities: Moderation Approach - Chelagat, Lelei Joy; Korir, Michael; Kibet, Yusuf (International Journal of Economics, Business and Management Studies, 2020)
The main aim of the study was to assess moderating role of organizational citizenship behaviour on relationship between employee political skill and employee performance in Kenyan universities. The study was grounded on social exchange theory. The study used positivism paradigm, explanatory research design, and combination of simple random and stratified sampling on a target population of 6147 employees in selected universities in Kenya. A sample size of 567 academic and non-academic staff selected based on Yamane’s formula to determine selection of respondents to be served with structured questionnaires. The reliability of the data collection instrument was presented using Cronbach Alpha while factor analysis was used to validate the instrument. Data was analysed quantitatively with the aid of the Statistical Package for Social Science (SPSS 24.0). Findings from Hayes model 1 showed that there is a positive and significant moderating effect of Organizational Citizenship Behaviour (R-sqΔ=.14, β= .48, p=.00) on the relationship between employee political skill and employee performance. Conclusively, Organizational Citizenship Behaviour significantly affects the relationship between Employee Political skill and Employee Performance. The study recommends leaders in institutions to instil the resource of employee political skill through a blend of organizational citizenship behaviour so as to enrich performance among employees. Additionally, it calls for broadening research and utilizing the existing theories on this topic on a global view.